2004
DOI: 10.1007/s10157-004-0324-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanisms of tubulointerstitial injury in IgA nephropathy: a new therapeutic paradigm in the prevention of progressive renal failure

Abstract: IgA nephropathy (IgAN) runs a highly variable clinical course with frequent involvement of tubulointerstitial damage. Notably, renal progression correlates more closely with the severity of tubulointerstitial lesions than with the degree of glomerular lesions In IgAN. Mesangial IgA deposition induces local release of cytokines, complement, and angiotensin II leading to glomerular inflammation. It remains unclear how mesangial IgA deposition leads to tubulointerstitial injury in IgAN. Moreover, IgA deposits are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…A substantial body of experimental and clinical data support the role of apoptosis in the pathogenesis of inflammatory tissue injury in critical illness including acute lung injury and ARDS, myocardial infarction, and renal and gastrointestinal tract failure dysfunction in sepsis (52,(70)(71)(72). Although apoptosis is vital in many physiologically important processes, either inappropriate activation or inhibition of apoptosis can lead to disease, either because cells have prolonged survival (ongoing inflammation) or because they die prematurely and produce structural and functional changes in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of experimental and clinical data support the role of apoptosis in the pathogenesis of inflammatory tissue injury in critical illness including acute lung injury and ARDS, myocardial infarction, and renal and gastrointestinal tract failure dysfunction in sepsis (52,(70)(71)(72). Although apoptosis is vital in many physiologically important processes, either inappropriate activation or inhibition of apoptosis can lead to disease, either because cells have prolonged survival (ongoing inflammation) or because they die prematurely and produce structural and functional changes in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Much attention has recently been focused on inflammatory injuries generated by a positive feedback loop in tubular epithelial cells (TEC) ultimately leading to renal failure [4]. Although pharmacological blockade of the renin angiotensin system (RAS) has become the therapeutic mainstay of tubulointerstitial injury in various glomerular diseases including IgAN, a complete blockade of the RAS with the present dose regimen may not be always possible.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sekiguchi et al [21 ]and Chan et al [22] reported that angiotensin II can lead to inflammatory responses through an NF-ĸB-dependent pathway, and that angiotensin II induces an increase in TGF-β in vascular smooth muscles and in mesangial cells [23, 24]. In this context, ARB has been shown to reduce fibrosis in a large number of disease models [25].…”
Section: Discussionmentioning
confidence: 99%